Development of a sensitive polymerase chain reaction (PCR) and digoxigenin (DIG)-labeled in situ hybridization (ISH) for the detection of Vibrio bacteria in the Pacific oyster Crassostrea gigas - Gary F. Kett (Elsevier, 2022)
Vibrio bacteria are one of the greatest threats to aquaculture, with Vibrio-associated mass mortality events occurring in all life stages worldwide. Vibrio aestuarianus is particularly problematic in Pacific oyster Crassostrea gigas cultures. A diagnostic method used to detect V. aestuarianus is quantitative (q)PCR and a confirmatory method is fluorescent in situ hybridization (FISH). These methods require specialized equipment and incur high costs. The objective of this study was to develop a novel generic (relating to a genus) PCR and DIG-labeled in situ hybridization (ISH) for the detection and confirmation of Vibrio. A PCR that detects all Vibrio spp. is particularly useful for blanket screening of hosts and environmental samples, while ISH facilitates the visual localization of bacteria. Both diagnostic methods were developed to be used synchronously with other methods that are specific to certain Vibrio spp. Primers (VibF3/VibR3) were designed to amplify a 286 bp product from the 16S ribosomal RNA gene common to all Vibrio spp. and to form the ISH probe. Confirmatory positive and negative controls were used in both methods. Results were compared with a V. aestuarianus specific qPCR protocol. Direct Sanger sequencing of PCR products, Blastn analysis and Clustal Omega alignments were used to confirm Vibrio sp. detection and assess similarity. Pathologies observed in C. gigas tissues were similar to those described in other studies. A positive ISH signal was observed in qPCR and PCR positive oysters and no signal was detected in uninfected individuals. These techniques will increase the diagnostic arsenal against this globally significant genus of bacteria.